Exploring space : women who led the way - Dickmann, Nancy (New York, NY : Children's Press, an imprint of Scholastic Inc., 2022)
From studying stars and discovering comets to flying into space as pioneering astronauts, women have been central to learning about space. Female astronomers gave us our first understanding of how large the universe really is and how much matter it contains. They were key to designing humans' first rocket-powered flights into space. And as soon as women could go into space themselves, they were eager to do so: some 65 women have now become space travelers. This book tells their stories and describes their vital contributions.
Henrietta Swan Leavitt -- Katherine Johnson -- Stephanie Wilson -- Andrea Ghez -- Hypatia -- Maria Kirch -- Wang Zhenyi -- Annie Jump Cannon -- Mary Golda Ross -- Valentina Tereshkova -- Mae Jamison -- Diana Trujillo.
School Library Journal, April 2022
Booklist, August 2022
Includes bibliographical references (page 48) and index.
6.2
3-6
860L
Keywords: Women astronauts -- Biography -- Juvenile literature; Women scientists -- Biography -- Juvenile literature; Women in astronautics -- History -- Juvenile literature; Women astronauts; Women scientists; Women in astronautics -- History; Women -- Biography; Biographies